Sustainable Development-Based Environmental Dispute Resolution Through Alternative Dispute Resolution in Indonesia - Sherly Widia Putri; Evi Dwi Hastri (Res Judicata Law Review, 2024)
Environmental problems are part and responsibility of all human beings who feel they want to live on this earth. Over time, the dynamics of community activities such as exploration, construction and exploitation activities in all fields, including industrial development, algiculture business (agriculture, plantations and fisheries), property and so on are growing very rapidly. The occurrence of disputes or conflicts that can be resolved one of them by means of out-of-court settlement using ADR (Alternative Dispute Resolution) or alternative dispute resolution (APS) or by means of Negotiation, Conciliation, Mediation, and Arbitration. The research method used is Normative Juridical research where the legal research method is carried out by examining library materials or secondary materials only. The purpose of this writing is expected to provide a view of how case studies occur in resolving environmental disputes through alternative channels or out of court. The results of this study indicate that environmental disputes can be resolved through non-litigation efforts where the Government must be consistent with sustainable development programs to prevent environmental disputes, where in the process and achievement of development there must be a balance between economic, social and ecosystem preservation and protection.